Circulating Tumor Cell Phenotype Predicts Recurrence and Survival in Pancreatic Adenocarcinoma. Issue 6 (December 2016) - Poruk, Katherine E.; Valero, Vicente; Saunders, Tyler; Blackford, Amanda L.; Griffin, James F.; Poling, Justin; Hruban, Ralph H.; Anders, Robert A.; Herman, Joseph; Zheng, Lei; Rasheed, Zeshaan A.; Laheru, Daniel A.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: We assessed circulating tumor cells (CTCs) with epithelial and mesenchymal phenotypes as a potential prognostic biomarker for patients with pancreatic adenocarcinoma (PDAC). Background: PDAC is the fourth leading cause of cancer death in the United States. There is an urgent need to develop biomarkers that predict patient prognosis and allow for better treatment stratification. Methods: Peripheral and portal blood samples were obtained from 50 patients with PDAC before surgical resection and filtered using the Isolation by Size of Epithelial Tumor cells method. CTCs were identified by immunofluorescence using commercially available antibodies to cytokeratin, vimentin, and CD45. Results: Thirty-nine patients (78%) had epithelial CTCs that expressed cytokeratin but not CD45. Twenty-six (67%) of the 39 patients had CTCs which also expressed vimentin, a mesenchymal marker. No patients had cytokeratin-negative and vimentin-positive CTCs. The presence of cytokeratin-positive CTCs ( P < 0.01), but not mesenchymal-like CTCs ( P = 0.39), was associated with poorer survival. The presence of cytokeratin-positive CTCs remained a significant independent predictor of survival by multivariable analysis after accounting for other prognostic factors ( P < 0.01). The detection of CTCs expressing both vimentin and cytokeratin was predictive of recurrence ( P = 0.01). Among patients with cancer recurrence, those with vimentin-positive and cytokeratin-expressing CTCs had decreased median time to recurrence compared with patients without CTCs ( P = 0.02). Conclusions: CTCs are an exciting potential strategy for understanding the biology of metastases, and provide prognostic utility for PDAC patients. CTCs exist as heterogeneous populations, and assessment should include phenotypic identification tailored to characterize cells based on epithelial and mesenchymal markers.